Essays on labor economics and inequality - Riedel, Lukas (2024)
In this dissertation, I collect four articles from the fields of labor economics and inequality and their intersection. As both fields are wide, I cover a subsection of topics that ranges from the measurement of gender inequality in the labor market over the evaluation of policies that address it to the broader question of assessing post-tax income inequality. Specifically, the first two chapters focus on female labor supply and gender inequality in the context of childbirth, the subsequent two move to inequality among women and general inequality. The dissertation evaluates public policies and methods to analyze them as well as it proposes methodological improvements.